The globalization of regional clusters: between localization and internationalization - Fornahl, Dirk; Grashof, Nils (New horizons in regional science series, 2021)
Addressing the role of regional clusters in the context of ongoing globalization, this timely book investigates the two seemingly competing trends of globalization and localization from both quantitative and qualitative perspectives. International case studies offer pioneering insights into the internationalization process of regional clusters and the effect of this on regional as well as firm performance.